Macedonian and Albanian interpretations of the Balkan Wars: the collision of historical narratives - Vankovska, Biljana (Филозофски факултет, Скопје, 2013)
This article deals with the collective memories and legacies of the Balkan wars (1912/1913) as they are enshrined in the popular memory of the Macedonians and the Albanians in the Republic of Macedonia. The focal point is on the political in memory;i.e. an attempt is made to examine remembrance of those past events among the public opinion-makers and the impact of memory on the general public and on the current political developments. The relationship between the ‘real’ history (history as it actually was) and the cognitive history of the Balkan wars (history as it is perceived) is portrayed as it is seen by the two dominant ethnic groups. The basic premise is that so-called ‘subjective history’ (which consists of perceptions, emotions, and attitudes) is in the minds of today’s actors so it affects the beliefs and values underlying their actions much more than the historical facts and knowledge gained by professionals. The centennial of the Balkan wars proves that the two major ethnic communities share the same myth of victimization, yet it confronts rather than brings them together. Furthermore, it adds to the ongoing deepening of the societal division that threatens the existence of the political community.